ANALISIS PERSEPSI APARATUR PEMERINTAH DESA TERHADAP DANA DESA DI KECAMATAN TALANG EMPAT KABUPATEN BENGKULU TENGAH - Meiyudi Ardianto; Neri Susanti (UNIVED Press, 2018)
Meiyudi Ardianto, Neri Susanti; This study aimed to get the perception of the village apparatus to use village funds, the use of the village funds according to the ministerial decree of village No. 08 year of 2016. The study was conducted in Talang Empat district of Central Bengkulu regency with a number of villages as many as 15 villages. This study was used rating scale analysis method by means of questionnaires distributed in each village and direct face with the village government apparatus.The results of the study show the village government organization variable gain the value of 718, variable of the implementation of rural development gain the value of 706 while the community empowerment and development variable gain the value of 690 and rural communities with a value of 713 this means the village government apparatus strongly agreed with these activities. Therefore, the perception of the village government apparatus in accordance with the village government budget. But in fact, the village government apparatus do not fully understand about the use of village funds. This is because the variable of the implementation of the village government and development of rural communities do not use the village fundsKey Words: The village government apparatus, the village funds.